Daya Saing dan Faktor-Faktor yang Mempengaruhi Ekspor Nanas Indonesia - Rachma Safitri, Viola; Kartiasih, Fitri (Jurnal Hortikultura Indonesia, 2019)
This study aims to determine the general picture of pineapple production and export in Indonesia, analyze the competitiveness of Indonesian pineapple in seven main export destination countries, and analyze the factors that affect Indonesian pineapple exports in the main export destination of pineapple in 2001-2014. The methods used in this study are Revealed Comparative Advantage (RCA), Trade Specialization Index (ISP), Intra-Industry Trade (IIT), and panel data regression. The results of this study indicate that the high production of Indonesian pineapple has not been matched by an increase in the volume of pineapple exports. The RCA index shows that Indonesia is superior to the Philippines in several countries such as the Netherlands, Germany, Singapore, Spain and Argentina for pineapple commodities. The ISP and IIT indices show that Indonesia has a tendency as an exporting country. The variable competitiveness index, the real exchange rate of the rupiah against the destination country currency, the income per capita of the destination country, and the amount of Indonesian pineapple production have a positive influence on the growth of the volume of pineapple exports in the seven main export destination countries while the price of pineapple real exports has a negative influence on the volume of pineapple exports in the seven main export destination countries.Keywords: competitiveness, panel data, pineapple exports, RCA